Menelaah Marcion Mengenai Paham Kesatuan Allah Perjanjian Lama dan Perjanjian Baru: Sebuah Riset Kesejarahan - Tirai Niscaya Harefa; Alon Mandimpu Nainggolan (Institut Agama Kristen Negeri Manado, 2022)
This article aims to approach the whole study using historical methods which are included in the research group with a qualitative paradigm. The historical in question is Marcion, a theologian who influenced Christianity in the second century. One of the teachings highlighted by Marcion is the understanding of God, where he rejects the God of the Old Testament but believes in the God of the New Testament that this rejection causes Marcion to reject the canon of the Old Testament. In the nineteenth century, two theologians who followed Marcion's ideology reappeared. That is why Marcion's theology becomes the rationale for research as an awareness of the phenomena that can reappear in the present and in the future. This paper examines the background of Marcion's life to the things that influenced the birth of Marcion's understanding of the God of the Old Testament and the God of the New Testament, including the actions of the church at that time and the influence of Marcion which continued to grow until the nineteenth century, especially those affecting Friedrich Delitzsch and Adolf Harnack. . This paper also follows up on the research step by synthesizing the views of theologians about the fact that God's nature is comprehensive and constitutes a continuous unity through God's attributes. So that it is hoped that Marcionism or the teaching of dogma will not arise, doctrines that are interpreted by rejecting the canon of the Bible and can be justified.